2010
DOI: 10.1177/0963662510383924
|View full text |Cite
|
Sign up to set email alerts
|

Popularization by Argentine researchers: the activities and motivations of CONICET scientists

Abstract: This paper presents the findings of a survey on popularization activities by 1700 scientists in Argentina. The tool used for this research was a questionnaire containing 21 questions on discipline, age, status in hierarchy, intensity of popularization activity, motives, difficulties and opinions on public issues and science policy. Our analysis of the data shows that patterns of public popularization in Argentina do not substantially differ from those found in two advanced countries, namely France and the Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
96
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(103 citation statements)
references
References 9 publications
3
96
0
4
Order By: Relevance
“…The equivalent figures are lower for Argentine researchers. Of a sample of Argentine researchers, only 10% said they had been interviewed for a radio program and 9% for a newspaper article within the previous year (36). In an Italian study, only 49% of the surveyed researchers reported media contacts in the previous 3 y (37).…”
Section: Frequency Of Scientists' Interactions With Journalistsmentioning
confidence: 99%
See 4 more Smart Citations
“…The equivalent figures are lower for Argentine researchers. Of a sample of Argentine researchers, only 10% said they had been interviewed for a radio program and 9% for a newspaper article within the previous year (36). In an Italian study, only 49% of the surveyed researchers reported media contacts in the previous 3 y (37).…”
Section: Frequency Of Scientists' Interactions With Journalistsmentioning
confidence: 99%
“…Overall, researchers from the humanities and social sciences tend to have more interactions with the media than those from the sciences (24,36,48). The recent German survey of researchers found that, in "informatics," "mathematics," "chemistry" and "material science," little more than 10% of researchers reported frequent media contacts; in "communication studies," "law," "history," "archaeology," and "philosophy," this proportion exceeded 50% (Fig.…”
Section: Frequency Of Scientists' Interactions With Journalistsmentioning
confidence: 99%
See 3 more Smart Citations